Marriage: an institution you cannot disparage? Evidence on the marriage norms of entrepreneurs - Isabell Stamm; Fabian Bernhard; Jan-Philipp Ahrens; Baris Istipliler (Small Business Economics, 2023)
Entrepreneurship research increasingly acknowledges marriage as an important resource for long-term commitment to entrepreneurial ventures. At the same time, family scholars emphasize the deinstitutionalization of marriage in many countries, meaning that marriage as formalized and long-term companionship has lost importance. We contend that outdated ideological positions in entrepreneurship studies on marriage potentially obscure the more complex reality of the marriage norms of entrepreneurs. Using representative panel data from Germany, our study demonstrates that there is substantial heterogeneity among marriage norms internalized by entrepreneurs in various contexts. While entrepreneurs, on average, are less likely to internalize companion marriage norms than the general population, family entrepreneurs are significantly more likely to internalize companion marriage norms. We provide new insight into the link between marriage norms and entrepreneurship and open promising new areas of inquiry with regard to social norms and entrepreneurial activity.
Keywords: L26; Z10; Z13; 330; Embeddedness; Marriage; Norms; Entrepreneurship; Deinstitutionalization